Indications for Autologous and Allogeneic Hematopoietic Stem-Cell Transplantation in Adults: State of the Art - Andrea Duminuco; Giuseppe A. Palumbo; Eleonora Avella; Alessandra Cupri; Bruno Garibaldi; Miriana Carmela Limoli; Elisa Mauro; Simona Patti; Nicolò Risata; Serena Romano; Flavia Schillaci; Andrea Spadaro; et al. (Journal of Clinical Medicine, 2026)
Hematopoietic stem-cell transplantation (HSCT) has evolved from a salvage procedure for otherwise-fatal leukemia into a curative modality spanning nearly every hematological malignancy and several non-malignant disorders. The contemporary landscape has been reshaped by three converging forces: the refinement of disease-specific risk stratification (European LeukemiaNet [ELN] 2022 for acute myeloid leukemia, Molecular International Prognostic Scoring System [IPSS-M] for myelodysplastic syndromes, Mutation-Enhanced International Prognostic Scoring System [MIPSS70+ v2.0], and Myelofibrosis Transplant Scoring System [MTSS] for myelofibrosis); the integration of measurable residual disease (MRD) into dynamic, response-adapted transplant decisions; and the approval of immune effector cell therapies that have displaced transplantation from several long-standing indications while creating new ones (bridge-to-transplant, post-CAR-T consolidation). In parallel, post-transplant cyclophosphamide (PTCy) has largely equalized outcomes across matched sibling, matched unrelated, and mismatched alternative donors, and novel agents (ruxolitinib, belumosudil, axatilimab) have materially reduced graft-versus-host disease (GVHD) morbidity. This narrative review synthesizes current indications for autologous (auto-HSCT) and allogeneic (allo-HSCT) transplantations in adults, and flags areas of persistent controversy where randomized data are still maturing. Across all indications, the clinician’s question is shifting from “transplant or not?” towards “which donor, which conditioning, which bridge, and which post-transplant maintenance?”, each tailored to disease biology, MRD trajectory, and patient fitness.